Evaluasi Program ˜Green Act'sebagai Tanggung Jawab Sosial PT Pertamina (Persero) - Lestari, Annisa Dieni; Hermawan, Aji; Kirbrandoko, Kirbrandoko (Jurnal Aplikasi Manajemen, 2016)
Environment conditions in Indonesia is degraded due to the operations of PTPertamina (Persero) which runs their corporate social responsibility on environmental fieldÂ aspects as a form of corporate responsibility towards the environment and the community. AnÂ education program of environmental empowering that has been running is Green Act'. TheÂ program was intended for 12 high schools (period I in 2010) and 19 high schools (period IIÂ 2011/2012). The purpose of this study is to evaluate that program. This study took place atÂ two high schools in Jakarta and Bekasi cities. The study was started from October 2013 toÂ March 2014. The method used was the analysis of the Input-Process-Impact and ParticipatoryÂ CSR analysis. The evaluation shows that the implementation of ˜Green Act'program isÂ categorised as successfull after going through the process of planning, implementation, monitoring,Â and evaluation, which involved the participation of stakeholders and the role of the facilitator.